Screening of benzenesulfonamide in combination with chemically diverse fragments against carbonic anhydrase by differential scanning fluorimetry - Mikhail Krasavin; Stanislav Kalinin; Sergey Zozulya; Anastasiia Gryniukova; Petro Borysko; Andrea Angeli; Claudiu T. Supuran (Taylor & Francis Group, 2020)
The differential scanning fluorimetry (DSF) screening of 5.692 fragments in combination with benzenesulfonamide (BSA) against bovine carbonic anhydrase (bCA) delivered >100 hits that either caused, on their own, a significant thermal shift (ΔTm, °C) in the protein melting temperature or significantly influenced the thermal shift observed for BSA alone. Three hits based on 1,2,3-triazole moiety represent the periphery of the recently reported potent inhibitors of hCA II, IX and XII which were efficacious in vivo. Such a re-discovery of suitable BSA periphery essentially validates the new fragment-based approach to the discovery of future CAIs. Structures of other validated fragment hits are reported.